Heterocyclic heptacene analogs – 8H-16, 17-epoxydinaphto[2, 3-c:2′, 3′-g]carbazoles as charge transport materials. (January 2016) - Rimkus, Renaldas; Tumkevičius, Sigitas; Serevičius, Tomas; Komskis, Regimantas; Adomėnas, Povilas; Gruodis, Alytis; Jankauskas, Vygintas; Kazlauskas, Karolis; Juršėnas, Saulius
Abstract: Owing to extended π-electron system higher polyacenes are promising materials for organic electronics, however realization of higher conjugation of acenes results in their instability under ambient conditions. We now report on synthesis, optical and electrical characterization of nitrogen heteroatom containing heptacene analogs – 8 H -16, 17-epoxydinaphto[2, 3- c :2′, 3′- g ]carbazoles – decorated with various alkyl and aryl side-groups. V-shape geometry, incorporation of nitrogen heteroatom and introduced epoxy bridge ensure higher oxidative stability of the compounds as compared to analogous polyacenes. Additionally, the alteration of the molecular structure with various side-groups, either conjugated or non-conjugated, enabled the tuning of ionization potential from 4.7 eV to 5.5 eV with further gain in compound stability. This ensures of hole drift mobility up to 8 × 10 −4 cm 2 /(V s) at 1 MV/cm for thick wet-casted films under ambient conditions. Peculiarities of forbidden lowest excited states in the V-shaped N-heptacenes are revealed based on detailed optical characterization and density functional modeling. Graphical abstract: Highlights: Synthesis of V-shaped N-heptacene analogs. Substitution on V-shaped N-heptacene enables HOMO energy tuning from 4.7 to 5.5 eV. Hole drift mobility up to 8 × 10 −4 cm 2 /(V s) for wet casted films in air.